Life and Times of Baba Farid (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Baba Farid, also known as Baba Farid-ud-din Ganjshakar, was a 12th-century Sufi saint and poet from the Punjab region of South Asia. His contributions to Sufism, poetry, and the social and cultural fabric of the time have had a lasting impact on the region and beyond. Baba farid’s abode was at Ajodhan which is contemporarily located in Pakistan and is called as Pak-Pattan these days. His life of simplicity and full of austerity strikes contrast with eminent religious scholars of those times who used to live lavishly and had their khanqahs supported by some local sheriffs or amirs. His aura had such divine spiritual blessings that people from far and near flocked in crowds of hundreds and thousands to seek solace in his company. In this paper, we will investigate the life of Baba Farid in the historical context, his key contributions and his impact on society.